2017
DOI: 10.1186/s41121-017-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Smear layer and debris removal from dentinal tubules using different irrigation protocols: scanning electron microscopic evaluation, an in vitro study

Abstract: Background: This study investigated the ability of different irrigation protocols to keep dentinal tubules (DT) open and avoid their blockage by the smear layer (SL) during the cleaning and shaping procedure (CSP). Methods: Twenty-five extracted teeth were divided into five groups (n = 5): group 1, NaOCl was kept in the canal during instrumentation and then washed out with distilled water, and the canal was irrigated with NaOCl with EndoVac in between files; group 2, the same procedure as group 1, but NaOCl wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In the present study human extracted mandibular teeth of approximately the same dimensions were selected for standardization and their bulky roots which allow for easier splitting procedure with less risk of sample corruption which has been demonstrated in previous studies (18,19,20) . Crowns were not completely decoronated to ensure space for irrigation reservoir during cleaning, Standardized cavities were prepared to simulate internal root resorption using round bur at the same level from the apex this was to create equal, uniform cavities more over to ensure they were filled with the same amount of CGM (22,23) .…”
Section: Discussionmentioning
confidence: 97%
“…In the present study human extracted mandibular teeth of approximately the same dimensions were selected for standardization and their bulky roots which allow for easier splitting procedure with less risk of sample corruption which has been demonstrated in previous studies (18,19,20) . Crowns were not completely decoronated to ensure space for irrigation reservoir during cleaning, Standardized cavities were prepared to simulate internal root resorption using round bur at the same level from the apex this was to create equal, uniform cavities more over to ensure they were filled with the same amount of CGM (22,23) .…”
Section: Discussionmentioning
confidence: 97%
“…Canal disinfection requires chemical preparation as well as mechanical preparation. Canal disinfection substantially relies on irrigants because of the anatomic complexities of the pulp canal system [46]. Mechanical preparation will result in smear layer formation and chemical preparation will disinfect the parts that cannot be reached mechanically [47].…”
Section: Methods Of Smear Layer Removalmentioning
confidence: 99%
“…EDTA decalcifies dentin to an extent of 20-30 µm in 5 min [52]. The appropriate time for EDTA application to remove smear layer is about two minutes, but the thicker the smear layer is, the longer time of exposure should be [46]. MTAD (Mixture tetracycline citric acid and detergent) is a potent intracanal irrigant in regards to smear layer removal.…”
Section: Methods Of Smear Layer Removalmentioning
confidence: 99%
“…EDTA and NaOCl have been shown to be more effective in disinfecting and cleaning dentinal tubules when used sequentially than when used as independent agents. Wang et al [16] demonstrated that alternating the use of NaOCl and EDTA with water in between is more efficient in keeping dentinal tubules open during cleaning and shaping procedures that when using NaOCl or EDTA alone. While EDTA does not possess significant antimicrobial properties, it can enhance the effectiveness of other antimicrobial agents by allowing their dissemination into otherwise inaccessible dentinal tubules that can potentially harbor microorganisms [17].…”
Section: Introductionmentioning
confidence: 99%